PM2.5 induced liver lipid metabolic disorders in C57BL/6J mice - Zhang, Chenxiao; Ma, Tengfei; Liu, Chang; Ma, Ding; Wang, Jian; Liu, Meng; Ran, Jinjun; Wang, Xueting; Deng, Xiaobei (Frontiers in Endocrinology, 2023)
PM2.5 can cause adverse health effects via several pathways, such as inducing pulmonary and systemic inflammation, penetration into circulation, and activation of the autonomic nervous system. In particular, the impact of PM2.5 exposure on the liver, which plays an important role in metabolism and detoxification to maintain internal environment homeostasis, is getting more attention these years. In the present study, C57BL/6J mice were randomly assigned and treated with PM2.5 suspension and PBS solution for 8 weeks. Then, hepatic tissue was prepared and identified by metabolomics analysis and transcriptomics analysis. PM2.5 exposure can cause extensive metabolic disturbances, particularly in lipid and amino acids metabolic dysregulation.128 differential expression metabolites (DEMs) and 502 differently expressed genes (DEGs) between the PM2.5 exposure group and control group were detected. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses showed that DEGs were significantly enriched in two disease pathways, non-alcoholic fatty liver disease (NAFLD) and type II diabetes mellitus (T2DM), and three signaling pathways, which are TGF-beta signaling, AMPK signaling, and mTOR signaling. Besides, further detection of acylcarnitine levels revealed accumulation in liver tissue, which caused restricted lipid consumption. Furthermore, lipid droplet accumulation in the liver was confirmed by Oil Red O staining, suggesting hepatic steatosis. Moreover, the aberrant expression of two key transcription factors revealed the potential regulatory effects in lipid metabolic disorders, the peroxisomal proliferative agent-activated receptors (PPARs) including PPARα and PPARγ is inhibited, and the activated sterol regulator-binding protein 1 (SREBP1) is overexpressed. Our results provide a novel molecular and genetic basis for a better understanding of the mechanisms of PM2.5 exposure-induced hepatic metabolic diseases, especially in lipid metabolism.